Todo Brasileiro merece nível A : habitação multifamiliar para o programa minha casa minha vida energeticamente eficiente - Alves, André Felipe Moura (2012)
This thesis describes the theoretical, methodological and programmatic proposal for a multifamily residential building located in the urban expansion area of Parnamirim/RN, inserted in the program Minha Casa Minha Vida and level of energy efficiency "A", as the RegulamentoTécnico de Qualidade (RTQ-R/INMETRO) for residential buildings. The development project initially consists of procedures as the study of theoretical, architectural programming and cases studies. With the delimitation of a field solution, situated between the reference and the context, proposals are studied to determine the solution and architectural detailing of the proposal. The architectural program was built based on the method of Problem Seeking (Peña and Parshall, 2001) and research has highlighted aspects of reducing the environmental impact and of the program Minha Casa Minha Vida , among others. The design process was characterized by the incorporation of aspects reviewed and programmed, seeking them compatible and have an economically viable building, socio-spatial quality and energy efficient. The results show that it is possible to obtain a building that meets the constraints of the program that provides housing and energy efficiency level A - and many other environmental qualities and constructive, particularly through architectural design